2016
DOI: 10.1111/jdi.12453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dapagliflozin in addition to insulin therapy in Japanese patients with type 2 diabetes: Results of the interim analysis of 16‐week double‐blind treatment period

Abstract: IntroductionDapagliflozin treatment when added to insulin therapy in Japanese patients with type 2 diabetes remains to be evaluated.Materials and MethodsThis was a multicenter, randomized, double‐blind, parallel‐group, placebo‐controlled study to evaluate efficacy (at 16 weeks) and long‐term safety (at 52 weeks) of dapagliflozin in addition to insulin therapy. The interim analysis was carried out at week 16 to assess the efficacy and safety profiles. The patients receiving insulin (n = 182) were randomized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 27 publications
7
67
0
Order By: Relevance
“…This risk is further increased with the use of SGLT2 inhibitors, likely due to increased glucosuria . The reported incidence of genital infections and UTIs was lower in the present study than in comparable studies in other populations; however, similar results have been reported in other studies of SGLT2 inhibitors in Asian populations . Adverse events of renal function were infrequent in both treatment groups (2.2% and 3.8% for dapagliflozin and placebo, respectively), and were primarily reported in relation to variation in blood creatinine values in protocol‐mandated regular laboratory checks without clinically symptomatic AEs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This risk is further increased with the use of SGLT2 inhibitors, likely due to increased glucosuria . The reported incidence of genital infections and UTIs was lower in the present study than in comparable studies in other populations; however, similar results have been reported in other studies of SGLT2 inhibitors in Asian populations . Adverse events of renal function were infrequent in both treatment groups (2.2% and 3.8% for dapagliflozin and placebo, respectively), and were primarily reported in relation to variation in blood creatinine values in protocol‐mandated regular laboratory checks without clinically symptomatic AEs.…”
Section: Discussionsupporting
confidence: 75%
“…Most of the study population was Chinese (82%), potentially limiting the generalizability of the study findings to other Asian populations or the overall Asian population. However, similar results have been observed in a study of Japanese patients receiving dapagliflozin as add‐on to insulin, a pooled analysis of dapagliflozin as monotherapy or add‐on therapy to OADs in broader Asian populations, and in studies of other SGLT2 inhibitors plus insulin in Japanese populations . The short duration of the study (24 weeks) does not allow assessment of the durability of the observed effects.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, the recently reported Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients‐Removing Excess Glucose trial showed no difference in the benefits of SGLT2 inhibitor on cardiovascular disease prevention between the patients with insulin therapy and those without insulin therapy. Thus, insulin injection combined with SGLT2 inhibitors for those patients is then considered from the perspective of efficacy and safety, although the insulin secretory capacity of those patients might be lower. Before prescribing the SGLT2 inhibitor, checking the insulin requirement of those patients seems to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Figure b shows the changes in FPG levels from baseline, which were assessed in four PIO studies ( n = 1,116) and six SGLT2i studies ( n = 1,683). Both the PIO/INS and SGLT2i/INS groups showed significantly reduced FPG levels compared with the respective PCB/INS group ( P < 0.001 for both).…”
Section: Resultsmentioning
confidence: 99%